PEMBERDAYAAN MASYARAKAT KAWASAN WISATA DESA BULUH CINA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Krisna Alim Nuswantoro; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted in Buluh Cina Village, Siak Hulu District, Kampar Regency. The background for raising this issue is to discuss the tourism potential of Buluh Cina Village. As a tourist village that has a lot of natural potential, but until now it has not been maximized properly, therefore researchers want to know the model of community empowerment and destination development. This thesis also aims to analyze the obstacles found in developing tourism potential in Buluh Cina Village. This thesis is a qualitative research with a descriptive approach. The data used are primary and secondary methods. The data collection technique was carried out by means of observation, interviews, and documentation which all answered research problems regarding the tourism potential of Buluh Cina Village. The informants of this research were the people of Buluh Cina Village which consisted of the Village Head, Ninik Mamak, BKSDA (Natural Resources Conservation Agency), Community and Community Leaders. Based on the results of the research, it was found that community empowerment in Buluh Cina Village was obtained in developing their tourism potential using a community empowerment tourism approach, namely community life belief, generation education, community skills, community rules, customs, community-built relationships and community participation. As well as the obstacles found in developing tourist destinations, there is still a lack of capital in development and a network that is still not extensive, especially for disseminating unique information on tourist destinations in Buluh Cina Village.Keywords: Destinations, Tourism Potential, Empowerment